Periodontal disease in patients with ankylosing spondylitis. Issue 01 (6th January 2009) - Pischon, N; Pischon, T; Gülmez, E; Kröger, J; Purucker, P; Kleber, B-M; Landau, H; Jost-Brinkmann, P-G; Schlattmann, P; Zernicke, J; Burmester, G-R; Bernimoulin, J-P; et al.
Abstract : Objective: Ankylosing spondylitis (AS) and periodontal disease (PD) are characterised by dysregulation of the host inflammatory response, resulting in soft and hard connective tissue destruction. AS has been related to other inflammatory diseases, however, there is a paucity of data on whether AS is associated with inflammatory PD. Methods: The association between AS and PD was examined in 48 patients with AS and 48 healthy controls, matched for age and gender. AS was diagnosed according to the modified New York criteria. Periodontal examination included probing pocket depth (PPD), clinical attachment loss (CAL), plaque index (PI) and bleeding on probing (BOP). Potential risk factors of PD such as smoking, low education, alcohol consumption, body mass index (BMI), as well as chronic diseases associated with PD and AS were assessed through questionnaires. Results: In stepwise logistic regression, including AS status, age, gender, education, smoking, alcohol consumption and BMI, only AS status, age and education remained significant predictors of PD. Patients with AS had significant 6.81-fold increased odds (95% CI 1.96 to 23.67) of PD (defined as mean attachment loss >3 mm) compared to controls. The strength of the association was attenuated but remained statistically significant after further adjustment for plaque accumulation (odds ratio (OR) 5.48, 95% CI 1.37 to 22.00). Conclusions: The present study shows that patients with AS have a significantly higher risk of PD, strongly suggesting the need for close collaboration between rheumatologists, periodontists and dental hygienists when treating patients with AS.